MENTZER INDEX AS A SCREENING TOOL FOR IRON DEFICIENCY ANEMIA IN 6-12 YEARS OLD CHILDREN - Awais, Muhammad; Asad Ahmad; Alvina Farid; Husna Khan (Journal of Postgraduate Medical Institute, 2022)
Objective: To validate Mentzer Index as a screening tool for Iron Deficiency Anemia (IDA) in 6 to 12 years old children. Methodology: This cross-sectional validation study was conducted at the Department of Pediatrics, Combined Military Hospital, Peshawar and Department of Pediatrics, Khyber Teaching Hospital, Peshawar from February 2021 to January 2022. Following set inclusion and exclusion criteria, a sample of 419 participants were enrolled using non-probability convenience sampling. A pre-designed performa was used to extract all the data, which was analyzed using SPSS v.25.0. Validation statistics were applied on the data extracted Mentzer Index, which is used as screening tool for IDA. Results: The mean age of the sample was of 7.28±1.07 years, in which 174 (41.5%) were males and 245 (58.5%) females. Hemoglobin was recorded as 10.11±1.09 g/dl, hematocrit as 31.82±2.56%, Serum Ferritin as 24.46±27.28 µg/l, Mean Corpuscular Volume (MCV) as 65.09±8.31 fL and Red Blood Cell (RBC) as 5.17±0.705 x106 /µL. In validation statistics, sensitivity was 67.3%, specificity 93.8%, Positive Predictive Value (PPV) 80%, Negative Predictive Value (NPV) 88.6%, diagnostic accuracy as 86.63%. The area under curve was recorded as 0.805, which shows excellent discrimination between diseased and non-diseased. Conclusion: The study concludes that Mentzer Index has a better specificity, PPV, NPV, and diagnostic accuracy. Similarly a better area under the curve was recorded, which proves it to be an excellent discriminator.